Pressure-sensitive adhesive composition, pressure-sensitive adhesive made using the same, pressure-sensitive adhesive for polarizing plate, and image display device

JP7651246B2Active Publication Date: 2025-03-26MITSUBISHI CHEM CORP
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2019101170
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-07-10
Filing Date
2019-05-30
Publication Date
2025-03-26
Estimated Expiration
2039-05-30

AI Technical Summary

Benefits of technology

【0016】 本発明の粘着剤組成物を用いて得られる粘着剤は、高温環境下においても高い帯電防止性能と高い耐久性を両立できるものである。そして、本発明の粘着剤組成物は、種々の用途、とりわけ偏光板用に好適な粘着剤を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651246000001
    Figure 0007651246000001
  • Figure 0007651246000002
    Figure 0007651246000002
  • Figure 0007651246000003
    Figure 0007651246000003
Patent Text Reader

Abstract

To provide an adhesive composition that can achieve both of high antistatic performance and durability even under a severe high-temperature environment, when used as an adhesive for bonding between a polarizing plate (protection film) and a glass face of a liquid crystal cell, or the like, in the production of an image display device.SOLUTION: An adhesive composition contains an acrylic resin (A) containing a structural site derived from a macromonomer (a1) and an ionic compound (B). Relative to the acrylic resin (A) 100 pts.wt., the ionic compound (B) is 3-20 pts.wt. The ionic compound (B) has a melting point of 30°C or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive composition, and a pressure-sensitive adhesive, a pressure-sensitive adhesive for polarizing plates, and an image display device using the same; more specifically, the present invention relates to a pressure-sensitive adhesive composition that forms a pressure-sensitive adhesive that can achieve both high antistatic performance and durability even in a high-temperature environment, and a pressure-sensitive adhesive, a pressure-sensitive adhesive for polarizing plates, and an image display device using the same. [Background technology]

[0002] Conventionally, liquid crystal displays have been manufactured by laminating a polarizing plate, in which both sides of a polarizer made of a polyvinyl alcohol-based film or the like to which polarizing properties have been imparted are covered with protective films, on the surface of a liquid crystal cell in which an oriented liquid crystal component is sandwiched between two glass plates. The lamination of the polarizing plate on the surface of the liquid crystal cell is usually performed by contacting and pressing an adhesive layer provided on the surface of the polarizing plate against the surface of the liquid crystal cell.

[0003] The adhesive used to bond such a polarizing plate (protective film) to a liquid crystal cell (glass plate) is required to have durability such that it does not lift or peel off from the liquid crystal cell (glass plate), for example, in a high-temperature environment.

[0004] In order to improve such durability, pressure sensitive adhesives using acrylic resins copolymerized with macromonomers have been proposed (see, for example, Patent Document 1).

[0005] In addition, because liquid crystal cells are driven by controlling the voltage, static electricity can cause problems such as uneven display and breakdowns. Static electricity is generated when adhesive films are attached or peeled off, so as a countermeasure against static electricity, it is necessary to give the adhesive antistatic properties.

[0006] Furthermore, as liquid crystal cells have become thinner in recent years, warping of the liquid crystal cells in high temperature environments has become a problem, and pressure-sensitive adhesives for bonding polarizing plates to liquid crystal cells are also required to have high stress relaxation properties.

[0007] As such, an adhesive that combines an acrylic resin using a macromonomer with an ionic compound has been proposed as an adhesive that combines anti-warping properties for liquid crystal cells and anti-static properties (see, for example, Patent Document 2).

[0008] It is also known that adhesives using macromonomers are useful as adhesives for touch panels, and that adhesives with excellent antistatic properties can prevent malfunction of touch panels (see, for example, Patent Documents 3 and 4). [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Application Publication No. 8-209095 [Patent Document 2] International Publication No. 2015 / 141382 [Patent Document 3] JP 2013-18227 A [Patent Document 4] JP 2013-105154 A Summary of the Invention [Problem to be solved by the invention]

[0010] However, in order to impart the adhesives described in Patent Documents 1 and 2 with the high antistatic performance that has been demanded in recent years, it is necessary to use a large amount of an ionic compound. In that case, the constraint on the molecular chains by the macromonomer is canceled out by the plasticization of the adhesive by the ionic compound, resulting in a problem of reduced durability.

[0011] In addition, the adhesives described in Patent Documents 3 and 4 contain a large amount of ionic compounds in order to further improve the antistatic performance, but adhesives containing a large amount of ionic compounds are not sufficient in terms of durability in high temperature environments. Therefore, further improvements are required that can achieve both excellent antistatic performance and durability even when a large amount of ionic compounds is contained.

[0012] Under such circumstances, the present invention aims to provide a pressure-sensitive adhesive composition which forms a pressure-sensitive adhesive that can achieve both high antistatic performance and durability even in harsh high-temperature environments when the adherend is, for example, glass or metal such as a conductive layer used in image display members such as liquid crystal cells, and also to provide a pressure-sensitive adhesive, a pressure-sensitive adhesive for polarizing plates, and an image display device using the same. [Means for solving the problem]

[0013] However, the present inventors have conducted extensive research in light of these circumstances and have found that in a pressure-sensitive adhesive composition containing an acrylic resin (A) containing a structural portion derived from a macromonomer (a1) and an ionic compound (B), the durability decreases when a large amount of the ionic compound (B) is contained, but by using an ionic compound having a high melting point as the ionic compound (B), the entanglement of molecular chains derived from the macromonomer (a1) is less susceptible to the effect of plasticization by the ionic compound (B) and the entanglement is maintained, thereby obtaining a pressure-sensitive adhesive that can achieve both high antistatic performance and high durability, thereby completing the present invention.

[0014] That is, the gist of the present invention relates to a pressure-sensitive adhesive composition containing an acrylic resin (A) containing a structural portion derived from a macromonomer (a1) and an ionic compound (B), characterized in that the pressure-sensitive adhesive composition contains 3 to 20 parts by weight of the ionic compound (B) per 100 parts by weight of the acrylic resin (A), and the ionic compound (B) is an ionic compound having a melting point of 30°C or higher.

[0015] Furthermore, the present invention relates to a pressure-sensitive adhesive, a pressure-sensitive adhesive for polarizing plates, and an image display device, which use the pressure-sensitive adhesive composition. Effect of the Invention

[0016] The pressure-sensitive adhesive obtained by using the pressure-sensitive adhesive composition of the present invention can achieve both high antistatic performance and high durability even in a high-temperature environment. Furthermore, the pressure-sensitive adhesive composition of the present invention can provide a pressure-sensitive adhesive suitable for various applications, particularly for polarizing plates.

[0017] Furthermore, if the macromonomer (a1) is an acrylic macromonomer having a structure derived from an alkyl (meth)acrylate and a polar group-containing (meth)acrylate, it is preferred since it has excellent compatibility with other monomers and is easily copolymerized.

[0018] Furthermore, when the number average molecular weight of the macromonomer (a1) is from 1,000 to 50,000, a pressure-sensitive adhesive having excellent mechanical properties and durability can be obtained.

[0019] When the content of the macromonomer (a1) is 0.1 to 10% by weight based on the polymerization components constituting the acrylic resin (A), a pressure-sensitive adhesive having a better balance between antistatic properties and durability can be obtained.

[0020] When the acrylic resin (A) is an acrylic resin obtained by polymerizing a polymerization component containing a polar group-containing monomer (a3), it has excellent reactivity with a crosslinking agent.

[0021] When the acid value of the acrylic resin (A) is 30 mgKOH / g or less, a pressure-sensitive adhesive having excellent thermal stability can be obtained.

[0022] When the ionic compound (B) is at least one of a nitrogen-containing onium salt and an alkali metal salt, compatibility is improved, and a pressure-sensitive adhesive having excellent heat resistance can be obtained.

[0023] Furthermore, when the crosslinking agent (C) is contained, a crosslinked structure can be formed, and a pressure-sensitive adhesive with even greater durability can be obtained.

[0024] Furthermore, when a silane coupling agent (D) is contained, a pressure-sensitive adhesive having even more excellent durability can be obtained.

[0025] The pressure-sensitive adhesive of the present invention is obtained by crosslinking the above-mentioned pressure-sensitive adhesive composition with the crosslinking agent (C), and therefore has both superior antistatic properties and durability.

[0026] The surface resistivity of the adhesive layer of the above adhesive is 1.0×10 10 Ω / cm 2 When it is less than this, the antistatic performance becomes even more excellent.

[0027] Furthermore, when the above-mentioned adhesive is used as an adhesive for bonding an image display member such as a polarizing plate (protective film) to a liquid crystal cell (glass plate) or a metal surface (conductive layer), the adhesive has both good antistatic performance and high durability, making the adhesive of the present invention extremely useful as an adhesive for polarizing plates.

[0028] An image display device formed by bonding a polarizing plate and an image display member such as a liquid crystal cell with the above pressure-sensitive adhesive is of excellent quality without causing display unevenness or peeling due to static electricity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] The present invention will be described in detail below. In the present invention, "(meth)acrylic" means acrylic or methacrylic, "(meth)acryloyl" means acryloyl or methacryloyl, and "(meth)acrylate" means acrylate or methacrylate. Also, "acrylic resin" means a resin obtained by polymerizing a polymerization component containing at least one (meth)acrylate monomer.

[0030] The pressure-sensitive adhesive composition of the present invention contains an acrylic resin (A) containing a structural moiety derived from a macromonomer (a1) and an ionic compound (B).

[0031] <Acrylic resin (A)> The acrylic resin (A) used in the present invention is a resin containing and polymerizing a macromonomer (a1) as a polymerization component. In addition to this macromonomer (a1), the acrylic resin (A) is an acrylic resin obtained by polymerizing a polymerization component containing a (meth)acrylic acid alkyl ester (a2), preferably a polar group-containing monomer (a3) ​​(excluding the macromonomer (a1)), and, if necessary, other copolymerizable monomers (a4).

[0032] [Macromonomer (a1)] The macromonomer (a1) refers to a high molecular weight monomer having a polymerizable functional group, and it is particularly preferred that the macromonomer has a polymerizable unsaturated group at the end of the polymer chain.

[0033] The number average molecular weight (Mn) of the macromonomer (a1) is preferably 1,000 to 50,000 in terms of the mechanical properties and durability of the resulting pressure-sensitive adhesive. The lower limit of Mn of the macromonomer (a1) is more preferably 2,000 or more, even more preferably 3,000 or more, and particularly preferably 3,500 or more. The upper limit of Mn of the macromonomer (a1) is more preferably 30,000 or less, even more preferably 20,000 or less, and particularly preferably 10,000 or less. If Mn is the lower limit or more, the cohesive force when made into the acrylic resin (A) tends to be improved and the durability tends to be excellent, which is preferable. On the other hand, if Mn is the upper limit or less, the coating suitability of the resin solution tends to be good and a uniform coating film tends to be easily obtained.

[0034] The number average molecular weight (Mn) is a number average molecular weight calculated based on the molecular weight of standard polystyrene, and is measured using a high performance liquid chromatograph (manufactured by Waters, "ACQUITY APC System") with four columns connected in series: one ACQUITY APC XT 450, one ACQUITY APC XT 200, and two ACQUITY APC XT 45.

[0035] The glass transition temperature (Tg) of the macromonomer (a1) is preferably from -100 to 150°C, more preferably from -70 to 130°C, and even more preferably from -50 to 120°C, from the viewpoint of durability. Furthermore, if the glass transition temperature of the macromonomer (a1) is 0° C. or lower, the pressure-sensitive adhesive using the acrylic resin (A) copolymerized with the macromonomer (a1) tends to have excellent antistatic properties. The glass transition temperature (Tg) of the macromonomer (a1) can be calculated, for example, from the monomer units constituting the macromonomer (a1) and their content ratio by the Fox formula described below.

[0036] [Raw material monomer for macromonomer (a1)] Examples of raw material monomers for obtaining the macromonomer (a1) include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-lauryl (meth)acrylate, and n-stearyl (meth)acrylate; hydroxyl group-containing (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and glycerol (meth)acrylate; Carboxy group-containing vinyl monomers such as (meth)acrylic acid, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxypropyl phthalic acid, 2-(meth)acryloyloxyethyl maleic acid, 2-(meth)acryloyloxypropyl maleic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxypropyl succinic acid, crotonic acid, fumaric acid, maleic acid, itaconic acid, monomethyl maleate, and monomethyl itaconate; Vinyl monomers containing an acid anhydride group, such as maleic anhydride and itaconic anhydride; Epoxy group-containing vinyl monomers such as glycidyl (meth)acrylate, glycidyl α-ethyl acrylate, and 3,4-epoxybutyl (meth)acrylate; Amino group-containing (meth)acrylate vinyl monomers such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate; Vinyl monomers containing an amide group, such as (meth)acrylamide, Nt-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, diacetone acrylamide, maleic acid amide, and maleimide; Vinyl monomers such as styrene, α-methylstyrene, vinyltoluene, (meth)acrylonitrile, vinyl chloride, vinyl acetate, and vinyl propionate; Divinylbenzene, ethylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, allyl (meth)acrylate, etc. These raw material monomers can be used alone or in combination of two or more kinds.

[0037] Furthermore, from the viewpoint of durability, it is preferable to have a polar group on the side chain of the macromonomer (a1). As a raw material monomer capable of having a polar group on the side chain, for example, at least one polar group-containing monomer selected from the group consisting of hydroxyl group-containing (meth)acrylates, carboxyl group-containing vinyl monomers, acid anhydride group-containing vinyl monomers, amino group-containing (meth)acrylate-based vinyl monomers, and amide group-containing vinyl monomers is used. Among the polar group-containing monomers, hydroxyl group-containing (meth)acrylates are preferred from the viewpoint of durability.

[0038] Furthermore, it is particularly preferable to use an alkyl(meth)acrylate or a polar group-containing (meth)acrylate as the raw material monomer for the macromonomer (a1), and it is particularly preferable from the viewpoint of durability that the macromonomer (a1) is an acrylic macromonomer having a structure derived from the alkyl(meth)acrylate or the polar group-containing (meth)acrylate, and in particular, an acrylic macromonomer obtained by polymerizing the alkyl(meth)acrylate or the polar group-containing (meth)acrylate.

[0039] Among the above raw material monomers, it is preferable to use (meth)alkyl acrylates having 1 to 8 carbon atoms and hydroxyl group-containing (meth)acrylates. Furthermore, it is preferable to use methyl (meth)acrylate, n-butyl (meth)acrylate and 2-hydroxyethyl (meth)acrylate in terms of compatibility and copolymerizability with the other copolymerization components (a2) to (a4).

[0040] The content of the macromonomer (a1) is preferably 0.1 to 10% by weight, more preferably 0.2 to 5% by weight, and even more preferably 0.5 to 2% by weight, based on the polymerization components constituting the acrylic resin (A). Within this content range, the balance between antistatic performance and durability is better.

[0041] [(Meth)acrylic acid alkyl ester (a2)] The (meth)acrylic acid alkyl ester (a2) may, for example, be one in which the number of carbon atoms in the alkyl group is usually 1 to 20 (preferably 1 to 18, particularly preferably 1 to 12, and further preferably 1 to 8), preferably an aliphatic (meth)acrylic acid alkyl ester, and specifically, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, n-propyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, etc. These may be used alone or in combination of two or more.

[0042] Among these (meth)acrylic acid alkyl esters (a2), methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred from the viewpoints of excellent adhesive properties and excellent stability during polymerization, and n-butyl (meth)acrylate is particularly preferred.

[0043] The content of the (meth)acrylic acid alkyl ester (a2) is preferably 10% by weight or more, particularly preferably 30% by weight or more, further preferably 50 to 99.9% by weight, particularly preferably 60 to 99.9% by weight, based on the polymerization components constituting the acrylic resin (A). If the content is too low, the adhesive properties and durability tend to decrease.

[0044] In terms of excellent compatibility with the ionic compound (B), it is preferable that the acrylic resin (A) contains methyl (meth)acrylate, ethyl (meth)acrylate, or n-butyl (meth)acrylate as a polymerization component, and it is particularly preferable that the content of these is 10% by weight or more, further preferably 30% by weight or more, and especially preferably 40 to 99.9% by weight, based on the polymerization components constituting the acrylic resin (A).

[0045] [Polar group-containing monomer (a3)] Next, the polar group-containing monomer (a3) ​​will be described. The polar group-containing monomer (a3) ​​in the present invention refers to a copolymerizable ethylenically unsaturated monomer such as a hydroxyl group-containing monomer, a carboxyl group-containing monomer, or a nitrogen atom-containing monomer other than the macromonomer (a1), and these can be used alone or in combination of two or more. In the present invention, it is preferable to contain at least one selected from the group consisting of a hydroxyl group-containing monomer, a carboxyl group-containing monomer, and a nitrogen atom-containing monomer.

[0046] Examples of the hydroxyl group-containing monomer include acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate; caprolactone-modified monomers such as caprolactone-modified 2-hydroxyethyl (meth)acrylate; oxyalkylene-modified monomers such as diethylene glycol (meth)acrylate and polyethylene glycol (meth)acrylate; primary hydroxyl group-containing monomers such as 2-acryloyloxyethyl-2-hydroxyethyl phthalate, N-methylol (meth)acrylamide, and hydroxyethyl acrylamide; secondary hydroxyl group-containing monomers such as 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 3-chloro 2-hydroxypropyl (meth)acrylate; and hydroxyl group-containing monomers such as 2,2-dimethyl 2-hydroxyethyl (meth)acrylate. These may be used alone or in combination of two or more.

[0047] Among the above hydroxyl group-containing monomers, primary hydroxyl group-containing monomers are preferred because of their excellent reactivity with the crosslinking agent (C), 2-hydroxyethyl(meth)acrylate is preferred because of its stability during polymerization, and 4-hydroxybutyl(meth)acrylate is preferred because it has a fast reactivity with the crosslinking agent (C) and shortens aging. Furthermore, 2-hydroxyethyl(meth)acrylate and 4-hydroxybutyl(meth)acrylate are preferred because they contain less impurities such as di(meth)acrylate during monomer preparation, and are easy to manufacture because they have high purity.

[0048] In addition, when the above-mentioned hydroxyl group-containing monomer is prepared and used, or when a commercially available product is used, it is also preferable to use one having a di(meth)acrylate content as an impurity of 0.5% by weight or less, particularly preferably 0.2% by weight or less, and further preferably 0.1% by weight or less. Specifically, 2-hydroxyethyl acrylate, 4-hydroxybutyl acrylate, and 2-hydroxypropyl acrylate having such impurity amounts are particularly preferred.

[0049] Examples of the carboxy group-containing monomer include (meth)acrylic acid and dimer acids of acrylic acid such as β-carboxyethyl acrylate, and among these, (meth)acrylic acid is preferred from the standpoint of heat resistance and stability during polymerization.

[0050] Examples of the nitrogen atom-containing monomer include amino group-containing monomers, amide group-containing monomers, and other nitrogen atom-containing monomers.

[0051] Examples of the amino group-containing monomer include primary amino group-containing monomers such as aminomethyl(meth)acrylate and aminoethyl(meth)acrylate, secondary amino group-containing monomers such as t-butylaminoethyl(meth)acrylate, and tertiary amino group-containing monomers such as ethylaminoethyl(meth)acrylate, dimethylaminoethyl(meth)acrylate, and diethylaminoethyl(meth)acrylate. Among the above amino group-containing monomers, tertiary amino group-containing monomers are preferred in terms of their high crosslinking promoting effect and high storage stability of the resin.

[0052] Examples of the amide group-containing monomer include (meth)acrylamide; alkoxyalkyl (meth)acrylamide monomers such as methoxymethyl (meth)acrylamide, ethoxymethyl (meth)acrylamide, propoxymethyl (meth)acrylamide, isopropoxymethyl (meth)acrylamide, n-butoxymethyl (meth)acrylamide, and isobutoxymethyl (meth)acrylamide; dialkyl (meth)acrylamide monomers such as dimethyl (meth)acrylamide and diethyl (meth)acrylamide; hydroxyl group-containing amide monomers such as N-(hydroxymethyl)acrylamide; and heterocyclic amide monomers such as (meth)acryloylmorpholine.

[0053] Among the above-mentioned amide group-containing monomers, (meth)acryloylmorpholine, alkoxyalkyl (meth)acrylamide monomers, and dialkyl (meth)acrylamide monomers are preferred in terms of the stability of the resin solution and the inhibition of migration of the ionic compound (B).

[0054] Among the various polar group-containing monomers (a3) ​​mentioned above, those containing a hydroxyl group are preferred in terms of excellent reactivity with the crosslinking agent (C).

[0055] From the viewpoint of ease of the crosslinking reaction, the molecular weight of the polar group-containing monomer (a3) ​​is preferably not more than 500. The lower limit of the molecular weight is usually 50.

[0056] The polar group-containing monomer (a3) ​​is preferably contained in an amount of 30% by weight or less based on the polymerization components constituting the acrylic resin (A) (hereinafter simply referred to as "polymerization components"). Among these, particularly when a hydroxyl group-containing monomer is used, the content is preferably 0.01 to 30% by weight, more preferably 0.1 to 20% by weight, particularly preferably 1 to 15% by weight, and even more preferably 3 to 10% by weight, from the viewpoints of durability and reworkability. Among the polar group-containing monomers (a3), when a carboxyl group-containing monomer is used, its content is preferably 0.01 to 10% by weight, more preferably 0.1 to 5% by weight, based on the polymerization components in terms of durability and reworkability. Also, from the viewpoints of corrosion resistance and suppression of hydrolysis of the substrate or adherend, its content is preferably 0.5% by weight or less, more preferably 0.2% by weight or less, particularly preferably 0.1% by weight or less, based on the polymerization components. When using a nitrogen atom-containing monomer among the polar group-containing monomers (a3), the content thereof is preferably 0.1 to 10% by weight, more preferably 0.5 to 5% by weight, based on the polymerization components in terms of durability and suppression of hydrolysis.

[0057] [Other copolymerizable monomers (a4)] The other copolymerizable monomer (a4) is a copolymerizable ethylenically unsaturated monomer, for example, aromatic ring-containing monomers such as benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, orthophenylphenoxyethyl (meth)acrylate; alicyclic ring-containing monomers such as cyclohexyl (meth)acrylate, cyclohexyloxyalkyl (meth)acrylate, t-butylcyclohexyloxyethyl (meth)acrylate, isobornyl (meth)acrylate, or dicyclopentanyl (meth)acrylate; 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, orthophenylphenoxyethyl (meth)acrylate; ) acrylate, 3-methoxybutyl (meth)acrylate, 2-butoxyethyl (meth)acrylate, 2-butoxydiethylene glycol (meth)acrylate, methoxydiethylene glycol (meth)acrylate, methoxytriethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxydipropylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, octoxypolyethylene glycol-polypropylene glycol-mono(meth)acrylate, lauroxypolyethylene glycol mono(meth)acrylate, stearoxypolyethylene glycol mono(meth)acrylate, and other ether chain-containing monomers. These may be used alone or in combination of two or more.

[0058] Among these, aromatic ring-containing monomers are preferred in terms of ease of adjusting the refractive index and birefringence and excellent light leakage resistance (light leakage resistance refers to the ability to prevent backlight light from leaking after high temperature or moist heat tests when used as an adhesive for bonding a polarizing plate to a liquid crystal cell or the like), and benzyl (meth)acrylate, phenoxy (meth)ethyl acrylate, and phenoxy diethylene glycol (meth)acrylate are particularly preferred. Alicyclic ring-containing monomers are preferred in terms of ease of adjusting the refractive index and birefringence and excellent adhesion to low-polarity adherends (e.g., cycloolefins, etc.).

[0059] The content of the other copolymerizable monomer (a4) is preferably 25% by weight or less based on the polymerization components in order not to impair the effects of the present invention.

[0060] The acrylic resin (A) used in the present invention can be produced by using a polymerization component obtained by appropriately selecting and combining a macromonomer (a1), preferably a (meth)acrylic acid alkyl ester (a2), a polar group-containing monomer (a3), and other copolymerizable monomers (a4), for example, by mixing or dropping such polymerization components and a polymerization initiator into an organic solvent and polymerizing them.

[0061] The polymerization reaction can be carried out by a conventionally known polymerization method such as solution radical polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc., among which solution radical polymerization and bulk polymerization are preferred, and solution radical polymerization is particularly preferred.

[0062] Examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbons such as toluene and xylene, aliphatic hydrocarbons such as hexane, esters such as ethyl acetate and butyl acetate, aliphatic alcohols such as n-propyl alcohol and isopropyl alcohol, and ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone.

[0063] Among these organic solvents, ethyl acetate, acetone, methyl ethyl ketone, butyl acetate, toluene, and methyl isobutyl ketone are preferably used from the viewpoints of ease of polymerization reaction, chain transfer effect, ease of drying during adhesive coating, and high safety, and particularly preferably ethyl acetate, acetone, and methyl ethyl ketone. These organic solvents may be used alone or in combination of two or more kinds. The amount of these organic solvents used is usually 10 to 900 parts by weight per 100 parts by weight of the polymerization components.

[0064] Examples of polymerization initiators used in such solution radical polymerization include azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, 4,4'-azobis(4-cyanovaleric acid), and 2,2'-azobis(methylpropionic acid), which are normal radical polymerization initiators, and organic peroxides such as benzoyl peroxide, lauroyl peroxide, di-t-butyl peroxide, and cumene hydroperoxide, which can be appropriately selected and used according to the monomer to be used. These polymerization initiators may be used alone or in combination of two or more. The amount of these polymerization initiators used is usually 0.01 to 5% by weight based on the polymerization components.

[0065] The acid value of the acrylic resin (A) thus obtained is preferably 30 mgKOH / g or less, particularly preferably 10 mgKOH / g or less, further preferably 5 mgKOH / g or less, and particularly preferably 1 mgKOH / g or less, from the viewpoints of thermal stability, low metal corrosivity, and excellent antistatic performance.

[0066] The acid value in the present invention is determined by neutralization titration using potassium hydroxide or potentiometric measurement.

[0067] The weight average molecular weight of the acrylic resin (A) is preferably 200,000 to 3,000,000, particularly preferably 400,000 to 2,000,000, further preferably 600,000 to 1,800,000, and particularly preferably 800,000 to 1,600,000. If the weight average molecular weight is too small, durability tends to decrease, whereas if it is too large, a large amount of dilution solvent is required during production, drying properties decrease, and the amount of residual solvent in the pressure-sensitive adhesive layer increases, tending to decrease durability.

[0068] The dispersity (weight average molecular weight / number average molecular weight) of the acrylic resin (A) is preferably 20 or less, particularly preferably 15 or less, and further preferably 10 or less. If the degree of dispersion is too high, reworkability and durability tend to decrease. The lower limit of the degree of dispersion is usually 1.

[0069] The weight-average molecular weights mentioned above are those calculated based on the molecular weight of standard polystyrene. The high-performance liquid chromatograph (Waters Japan, "Waters 2695 (main body)" and "Waters 2414 (detector)") was equipped with a Shodex GPC KF-806L column (exclusion limit molecular weight: 2 × 10 7 , Separation range: 100~2×10 7 The measurement is performed using three tubes (10,000 theoretical plates / tube, packing material: styrene-divinylbenzene copolymer, packing particle size: 10 μm) connected in series, and the number average molecular weight can be measured in the same way. The degree of dispersion can be calculated from the weight average molecular weight and the number average molecular weight.

[0070] The glass transition temperature (Tg) of the acrylic resin (A) is preferably −100 to 10° C., particularly preferably −70 to 0° C., and further preferably −65 to −25° C. If the glass transition temperature is too high, the antistatic performance tends to decrease, whereas if the glass transition temperature is too low, the ionic compound (B) serving as the antistatic agent tends to be easily mobile and bleed, resulting in decreased durability.

[0071] The glass transition temperature (Tg) is calculated by the following Fox formula.

number

[0072] That is, the glass transition temperature (Tg) of the acrylic resin (A) is a value calculated by applying the glass transition temperature and weight fraction of each monomer constituting the acrylic resin (A) as a homopolymer to the Fox equation. The glass transition temperature of the homopolymer of the monomers constituting the acrylic resin (A) is usually measured by a differential scanning calorimeter (DSC) and can be measured by a method in accordance with JIS K7121-1987 or JIS K 6240.

[0073] The viscosity of the acrylic resin (A) is adjusted with a solvent etc., and the acrylic resin (A) solution is used in the pressure-sensitive adhesive composition of the present invention. From the viewpoint of ease of handling, the viscosity of the acrylic resin (A) solution is preferably 500 to 20,000 mPa·s, particularly preferably 1,000 to 18,000 mPa·s, and further preferably 2,000 to 15,000 mPa·s. If the viscosity is too high, the fluidity decreases and handling tends to become difficult, whereas if the viscosity is too low, application of the resulting adhesive tends to become difficult.

[0074] The viscosity of the acrylic resin (A) solution is measured by a rotational viscometer using a B-type viscometer with the resin solution adjusted to 25°C.

[0075] Thus, the acrylic resin (A) used in the present invention is obtained.

[0076] <Ionic Compound (B)> The pressure-sensitive adhesive composition of the present invention further contains an ionic compound (B) from the standpoint of countermeasures against static electricity. The ionic compound (B) is a compound consisting of a cationic component and an anionic component, and is a compound consisting of a combination of an organic cation or an inorganic cation as the cationic component and an organic anion or an inorganic anion as the anionic component. The ionic compound (B) may be used alone or in combination of two or more kinds.

[0077] As the inorganic cation, an alkali metal cation is preferred from the viewpoint of antistatic performance, and a lithium cation is particularly preferred. Examples of organic cations include pyridinium cations, piperidinium cations, pyrrolidinium cations, cations having a pyrroline skeleton, cations having a pyrrole skeleton, imidazolium cations, tetrahydropyrimidinium cations, dihydropyrimidinium cations, pyrazolium cations, pyrazolinium cations, tetraalkylammonium cations, trialkylsulfonium cations, and tetraalkylphosphonium cations. Among the cationic components, organic cations are preferred, and in particular, nitrogen-containing organic cations are preferred in terms of compatibility with the resin, and tetraalkylammonium cations, pyridinium cations, and imidazolium cations are preferred in terms of compatibility with the acrylic resin (A).

[0078] Examples of the anion component include Cl. - , Br - , I - , AlCl4 - , Al2Cl7 - , BF4 - , PF6 - , ClO4 - , NO3 - , CH3COO - , CF3COO - , CH3SO3 - , CF3SO3 - , (CF3SO2)3C - , AsF6 - , SbF6 - , NbF6 - , TaF6 - , (C2O4)2B - , SCN - , (CN)2N - , C4F9SO3 - , C3F7COO - , (CF3SO2)(CF3CO)N - , - O3S(CF2)3SO3 - or those represented by the following general formulas (1) to (4) are used. (1): (C n F 2n+1 SO2)2N - (wherein n is an integer from 1 to 10), (2):CF2(C m F 2m SO2)2N - (where m is an integer from 1 to 10), (3): O3S (CF2) l SO3 - (wherein l is an integer from 1 to 10), (4): (C p F 2p+1 SO2)N - (C q F 2q+1 SO2), (where p and q are integers from 1 to 10) Among the above, anions containing a fluorine atom are particularly preferred, and fluorine-containing sulfonium anions, fluorine-containing imide anions and fluorine-containing sulfonylimide anions are more preferred in terms of antistatic performance, durability and compatibility with the acrylic resin (A).

[0079] As the ionic compound (B) of the present invention, a nitrogen-containing onium salt is preferred from the viewpoint of compatibility with the acrylic resin (A), and an alkali metal salt is preferred from the viewpoint of excellent heat resistance. The cation component and anion component constituting such a salt are appropriately selected from the combinations of the above-mentioned cation components and anion components.

[0080] Examples of the nitrogen-containing onium salt include tetrabutylammonium N,N-bis(trifluoromethanesulfonyl)imide (melting point: about 95°C), tetraethylammonium N,N-bis(trifluoromethanesulfonyl)imide (melting point: about 110°C), 1-octyl-3-methylpyridinium bisoxalatoborate (melting point: about 55°C), 1-octyl-3-methylnonafluorobutanesulfonate (melting point: 40.9°C), and 1-octylpyridinium hexafluorophosphate (melting point: 67.9°C). Preferred examples of the alkali metal salt include lithium N,N-bis(trifluoromethanesulfonyl)imide (melting point: 235° C.) and lithium trifluoromethanesulfonate (melting point: 423° C.).

[0081] From the viewpoint of the balance between antistatic performance and durability, the anion component of the ionic compound (B) is preferably a fluorine-containing anion, and among these, lithium trifluoromethanesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.) and lithium N,N-bis(trifluoromethanesulfonyl)imide (manufactured by Sanko Kagaku Co., Ltd.) are particularly preferably used.

[0082] The melting point of the ionic compound (B) is 30° C. or higher, more preferably 35° C. to 550° C., particularly preferably 40° C. to 500° C., and even more preferably 50° C. to 450° C. If the melting point is within this range, the constraint on the molecular chain of the acrylic polymer by the macromonomer (a1) is unlikely to decrease at high temperatures, resulting in good durability.

[0083] The content of the ionic compound (B) is 3 to 20 parts by weight, particularly preferably 4 to 15 parts by weight, and further preferably 5 to 12 parts by weight, based on 100 parts by weight of the acrylic resin (A). If the content of such ionic compound (B) is too low, the antistatic performance will be reduced, making it easier for static electricity to cause malfunction of the touch panel or uneven display of the liquid crystal cell. If the content is too high, the adhesive layer will plasticize or bleed, resulting in reduced durability.

[0084] <Crosslinking agent (C)> The pressure-sensitive adhesive composition of the present invention preferably contains a crosslinking agent (C) in addition to the acrylic resin (A) and the ionic compound (B). The crosslinking agent (C) is preferred in that it improves the adhesion to the substrate and improves the durability of the pressure-sensitive adhesive.

[0085] The crosslinking agent (C) reacts with the functional groups in the acrylic resin (A) to form a crosslinked structure, and examples thereof include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, aziridine-based crosslinking agents, melamine-based crosslinking agents, aldehyde-based crosslinking agents, amine-based crosslinking agents, metal chelate-based crosslinking agents, etc. Among these, it is preferable to use an isocyanate-based crosslinking agent in terms of improving adhesion to the substrate and excellent reactivity with the acrylic resin (A). The crosslinking agent (C) may be used alone or in combination of two or more kinds.

[0086] Examples of the isocyanate-based crosslinking agent include aromatic isocyanate-based crosslinking agents such as tolylene diisocyanate-based crosslinking agents such as 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, xylylene diisocyanate-based crosslinking agents such as 1,3-xylylene diisocyanate, diphenylmethane-4,4-diisocyanate and other diphenylmethane-based crosslinking agents, and naphthalene diisocyanate-based crosslinking agents such as 1,5-naphthalene diisocyanate; isophorone diisocyanate, 1,4-cyclohexane diisocyanate, and other diphenylmethane-based crosslinking agents. alicyclic isocyanate crosslinking agents such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and the like; and adducts, biuret forms, and isocyanurates of the above-mentioned isocyanate compounds.

[0087] Among these isocyanate-based crosslinking agents, tolylene diisocyanate-based crosslinking agents are preferred in terms of pot life and durability, xylylene diisocyanate-based crosslinking agents or isocyanurate skeleton-containing isocyanate-based crosslinking agents are preferred in terms of shortening the aging time, and aromatic ring-free isocyanate-based crosslinking agents are preferred in terms of yellowing resistance. Specifically, among these, tolylene diisocyanate, xylylene diisocyanate, an adduct of hexamethylene diisocyanate and trimethylolpropane, and a nurate are preferred in terms of excellent balance between durability, pot life, and crosslinking speed.

[0088] Examples of the epoxy crosslinking agent include bisphenol A-epichlorohydrin type epoxy resins, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl erythritol, and diglycerol polyglycidyl ether.

[0089] Examples of the aziridine-based crosslinking agent include tetramethylolmethane-tri-β-aziridinylpropionate, trimethylolpropane-tri-β-aziridinylpropionate, N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), and N,N'-hexamethylene-1,6-bis(1-aziridinecarboxamide).

[0090] Examples of the melamine-based crosslinking agent include hexamethoxymethylmelamine, hexaethoxymethylmelamine, hexapropoxymethylmelamine, hexaptoxymethylmelamine, hexapentyloxymethylmelamine, hexahexyloxymethylmelamine, melamine resins, and the like.

[0091] Examples of the aldehyde crosslinking agent include glyoxal, malondialdehyde, succindialdehyde, maleic dialdehyde, glutaric dialdehyde, formaldehyde, acetaldehyde, and benzaldehyde.

[0092] Examples of the amine-based crosslinking agent include hexamethylenediamine, triethyldiamine, polyethyleneimine, hexamethylenetetraamine, diethylenetriamine, triethyltetraamine, isophoronediamine, amino resins, and polyamides.

[0093] Examples of the metal chelate crosslinking agent include acetylacetone and acetoacetyl ester coordination compounds of polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium.

[0094] When such a crosslinking agent (C) is used, its content is preferably 0.005 to 30 parts by weight, particularly preferably 0.01 to 10 parts by weight, further preferably 0.03 to 5 parts by weight, and particularly preferably 0.05 to 3 parts by weight, relative to 100 parts by weight of the acrylic resin (A). If the content is too low, durability tends to be easily reduced, whereas if the content is too high, stress relaxation tends to be reduced, making the substrate more susceptible to warping or requiring long-term aging.

[0095] It is preferable to further blend a silane coupling agent (D) in the pressure-sensitive adhesive composition of the present invention, as long as the effect of the present invention is not impaired.

[0096] <Silane coupling agent (D)> The silane coupling agent (D) is an organosilicon compound that contains, in its structure, one or more reactive functional groups and one or more alkoxy groups bonded to a silicon atom, and is preferably contained in the pressure-sensitive adhesive composition of the present invention in order to improve durability.

[0097] Examples of the reactive functional group in the silane coupling agent (D) include an epoxy group, a (meth)acryloyl group, a mercapto group, a hydroxyl group, a carboxy group, an amino group, an amide group, an isocyanate group, and the like. Among these, an epoxy group and a mercapto group are preferred from the viewpoint of excellent durability and reworkability.

[0098] The content of the reactive functional group in the silane coupling agent (D) is preferably 3,000 g / mol or less, more preferably 1,500 g / mol or less, and even more preferably 800 g / mol or less. If it is within the above range, the balance between durability and reworkability tends to be excellent.

[0099] The alkoxy group in the silane coupling agent (D) preferably contains an alkoxy group having 1 to 8 carbon atoms from the viewpoints of durability and storage stability, and particularly preferably contains a methoxy group or an ethoxy group.

[0100] The silane coupling agent (D) may have an organic functional group other than the reactive functional group and the alkoxy group bonded to the silicon atom, such as an alkyl group or a phenyl group.

[0101] From the viewpoint of reworkability and durability, the silane coupling agent (D) preferably has a weight average molecular weight of 1,000 or more, more preferably 2,300 to 30,000, and particularly preferably 3,000 to 20,000. When the weight average molecular weight is within the above range, the balance between reworkability and durability tends to be excellent.

[0102] The weight average molecular weight mentioned above is a weight average molecular weight calculated based on the molecular weight of standard polystyrene, and can be measured by the following method. Equipment: Gel permeation chromatograph Detector: Differential refractive index detector RI (Tosoh Corporation, RI-8020 type, sensitivity 32) Column: TSKgel guardcolumn HHR-H (1 column) (Tosoh Corporation, φ6mm×4cm), TSKgel GMHHR-N (2 columns) (Tosoh Corporation, φ7.8mm×30cm) Solvent: Tetrahydrofuran (THF) Column temperature: 23℃ ·Flow rate: 1.0mL / min

[0103] The silane coupling agent (D) is preferably an oligomeric organosilicon compound (organosiloxane compound) such as a dimer or trimer formed by hydrolysis and polycondensation of a part of an organosilicon compound, from the viewpoint of reworkability and durability. Examples of such silane coupling agents include mercapto group-containing oligomeric silane coupling agents formed by hydrolysis and polycondensation of a part of a mercapto group-containing silane compound such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyldimethoxymethylsilane, and mercapto group-containing oligomeric silane coupling agents which are co-condensates of the above mercapto group-containing silane compound and an alkyl group-containing silane compound such as methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane, and the like; γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxy ... Examples of the epoxy group-containing oligomer type silane coupling agents include those obtained by hydrolyzing and polycondensing a part of an epoxy group-containing silane compound such as pyrtriethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropylmethyldimethoxysilane, methyltri(glycidyl)silane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; epoxy group-containing oligomer type silane coupling agents which are co-condensates of the above-mentioned epoxy group-containing silane compounds with alkyl group-containing silane compounds such as methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, and ethyltrimethoxysilane; and epoxy group-containing oligomer type silane coupling agents obtained by ether-modifying a part of these epoxy group-containing oligomer type silane coupling agents. These may be used alone or in combination of two or more.

[0104] The oligomer type silane coupling agent preferably has an alkoxy group content of 1 to 60% by weight, particularly preferably 3 to 50% by weight, and further preferably 5 to 25% by weight, from the viewpoint of an excellent balance between durability and reworkability.

[0105] Specific examples of the oligomer-type silane coupling agent include commercially available epoxy group-containing silane coupling agents manufactured by Shin-Etsu Chemical Co., Ltd., such as "KBM-403", "X-41-1053", "X-41-1059A", "X-24-9590", "KBM-803", "X-41-1805", "X-41-1810", and "X-41-1818".

[0106] When the silane coupling agent (D) is used, its content is preferably 0.001 to 3 parts by weight, particularly preferably 0.005 to 1 part by weight, further preferably 0.01 to 0.5 parts by weight, and particularly preferably 0.015 to 0.3 parts by weight, relative to 100 parts by weight of the acrylic resin (A). If the content is too low, reworkability tends to decrease, whereas if the content is too high, the silane coupling agent (D) tends to bleed, resulting in decreased durability.

[0107] <Other optional ingredients> Furthermore, the pressure-sensitive adhesive composition of the present invention may contain, as other optional components, various additives such as resin components, acrylic monomers, polymerization inhibitors, antioxidants, corrosion inhibitors, crosslinking accelerators, radical generators, peroxides, radical scavengers, UV absorbers, antioxidants, plasticizers, pigments, stabilizers, and fillers, metals, resin particles, etc. In addition to the above, the pressure-sensitive adhesive composition may contain small amounts of impurities contained in the manufacturing raw materials of the components of the pressure-sensitive adhesive composition.

[0108] When the above-mentioned other optional components are used, the content thereof is preferably 5 parts by weight or less, particularly preferably 1 part by weight or less, and further preferably 0.5 parts by weight or less, based on 100 parts by weight of the acrylic resin (A). If the content is too high, the compatibility with the acrylic resin (A) decreases, and the durability tends to decrease.

[0109] Thus, the pressure-sensitive adhesive composition of the present invention can be obtained by mixing the acrylic resin (A) and the ionic compound (B), and optionally the crosslinking agent (C), the silane coupling agent (D), and further other optional components.

[0110] The mixing method is not particularly limited, and various methods can be used, such as a method of mixing the components all at once, or a method of mixing any components and then mixing the remaining components all at once or sequentially.

[0111] The pressure-sensitive adhesive composition of the present invention can be made into a pressure-sensitive adhesive by curing (crosslinking), and further, an optical member with a pressure-sensitive adhesive layer can be obtained by laminating an adhesive layer made of such a pressure-sensitive adhesive on an optical member (optical laminate). The optical member with the pressure-sensitive adhesive layer preferably further has a release sheet provided on the surface of the pressure-sensitive adhesive layer opposite to the optical member surface.

[0112] The method for producing the pressure-sensitive adhesive layer-attached optical member includes the steps of: [1] A method in which a pressure-sensitive adhesive composition is applied onto an optical member, dried, and then a release sheet is attached thereto, followed by aging treatment at least at room temperature (23°C) or at an elevated temperature; [2] A method in which a pressure-sensitive adhesive composition is applied onto a release sheet, dried, and then an optical member is attached thereto, followed by aging treatment at least at room temperature or at an elevated temperature; Among these, the method (2) in which aging is performed at room temperature is preferred, since it does not damage the optical member and has excellent adhesiveness to the optical member. In the above, the optical member is particularly effective when it is a polarizing plate, but the above method can also be used when forming a pressure-sensitive adhesive layer on an adherend other than an optical member.

[0113] Such aging treatment is carried out to balance the adhesive properties as the reaction time of the chemical crosslinking of the adhesive, and the aging conditions are a temperature of 20 to 70°C and a time period of usually 1 to 30 days, and specifically, the aging may be carried out under conditions such as 1 to 20 days at 23°C, 3 to 10 days at 23°C, or 1 to 7 days at 40°C.

[0114] When applying the pressure-sensitive adhesive composition, it is preferable to dilute the pressure-sensitive adhesive composition in a solvent before application. The dilution concentration is preferably 5 to 60% by weight, particularly preferably 10 to 30% by weight in terms of solid content.

[0115] The solvent is not particularly limited as long as it dissolves the pressure-sensitive adhesive composition, and examples of the solvent that can be used include ester-based solvents such as methyl acetate, ethyl acetate, methyl acetoacetate, and ethyl acetoacetate, ketone-based solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, aromatic solvents such as toluene and xylene, and alcohol-based solvents such as methanol, ethanol, and propyl alcohol. Among these, ethyl acetate and methyl ethyl ketone are preferably used in terms of solubility, drying property, cost, etc. These can be used alone or in combination of two or more.

[0116] The pressure-sensitive adhesive composition can be applied by a conventional method such as roll coating, die coating, gravure coating, comma coating, or screen printing.

[0117] The gel fraction of the pressure-sensitive adhesive layer produced by the above method is preferably 30 to 98% by weight, particularly preferably 35 to 95% by weight, and further preferably 50 to 90% by weight, from the viewpoints of durability and suppression of a decrease in the degree of polarization. If the gel fraction is too low, the pressure-sensitive adhesive layer tends to foam in a high-temperature environment, whereas if the gel fraction is too high, lifting or peeling tends to occur easily.

[0118] The gel fraction is an indication of the degree of crosslinking (degree of curing) and is calculated, for example, by the following method: An adhesive is picked from an adhesive film formed by forming an adhesive layer on a substrate such as an optical member, particularly a polarizing plate, and the adhesive is wrapped in a 200-mesh SUS wire net and immersed in ethyl acetate adjusted to 23° C. for 24 hours, and the weight percentage of the insoluble adhesive component remaining in the wire net relative to the weight of the adhesive before immersion in ethyl acetate is defined as the gel fraction.

[0119] The pressure-sensitive adhesive layer produced by the above method preferably has a moderate tackiness when touched with the fingers, since this tends to improve workability due to good wettability when actually applied to an adherend.

[0120] As for the electrical properties of the pressure-sensitive adhesive layer obtained using the pressure-sensitive adhesive composition of the present invention, a low surface resistivity is preferable as a countermeasure against static electricity, and more preferably 1.0×10 10 Ω / cm 2 less than 8.0×10 9 Ω / cm 2 less than 5.0×10 9 Ω / cm 2 less than 4.0×10 9 Ω / cm 2 If the surface resistivity is too high, the adhesive is likely to be charged, and when used for liquid crystal display applications, display unevenness due to static electricity tends to occur.

[0121] In the present invention, the optical member with a pressure-sensitive adhesive layer, particularly the polarizing plate with a pressure-sensitive adhesive layer, is used, for example, as a liquid crystal display panel, by bonding the pressure-sensitive adhesive layer surface to a glass substrate directly, or after peeling off the release sheet in the case of a plate having a release sheet.

[0122] The pressure-sensitive adhesive composition of the present invention can provide a pressure-sensitive adhesive that can achieve both high antistatic performance and durability even in high-temperature environments, and is useful as a pressure-sensitive adhesive for optical components, in particular as a pressure-sensitive adhesive for polarizing plates that bond a polarizing plate to a glass substrate, etc.

[0123] Examples of protective films constituting a polarizing plate include triacetyl cellulose-based films, acrylic-based films, polyethylene-based films, polypropylene-based films, and cycloolefin-based films. The present invention can be suitably used for polarizing plates using any of these protective films, but a polarizing plate laminated with a cycloolefin-based film is particularly preferred in that the effects of the present invention can be easily obtained.

[0124] Furthermore, by using the above-mentioned pressure-sensitive adhesive, it is possible to prepare an image display device such as a liquid crystal display device by bonding a polarizing plate and a liquid crystal cell together, and the obtained image display device can be produced with high precision and has excellent durability. EXAMPLES

[0125] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are by weight.

[0126] First, various acrylic resins (A) were prepared as follows, and other raw materials for the adhesive composition were also prepared. The acid value, weight average molecular weight, dispersity, and glass transition temperature of the acrylic resins (A) were measured according to the methods described above. The viscosity was measured at 25°C using a Brookfield viscometer.

[0127] <Acrylic resin (A)> The following materials were prepared as raw materials for the acrylic resin (A) (see Table 1).

[0128] <Macromonomer (a1)> As the macromonomer (a1), the following was prepared. In addition, when calculating the glass transition temperature, the following values ​​were used as the glass transition temperature when each monomer was made into a homopolymer. Methyl methacrylate (MMA) 105℃ n-Butyl acrylate (BA) -56°C 2-Hydroxyethyl methacrylate (HEMA) 55°C

[0129] (Macromonomer 1): An acrylic macromonomer containing hydroxyl groups in the side chain, which is a polymer of methyl methacrylate (MMA) and 2-hydroxyethyl methacrylate (HEMA) (manufactured by Mitsubishi Chemical Corporation, MMA:HEMA (weight ratio) = 75.5:24.5, number average molecular weight 5,700, dispersity 1.6, calculated glass transition temperature 91°C)

[0130] (Macromonomer 2): Acrylic macromonomer containing polybutyl acrylate (PBA) as the main component (Kaneka Corporation, PBA = 100%, number average molecular weight 7,970, dispersity 1.2, calculated glass transition temperature -56°C)

[0131] (Macromonomer 3): Acrylic macromonomer containing polymethyl methacrylate (PMMA) as the main component (manufactured by Mitsubishi Chemical Corporation, PMMA = 100%, number average molecular weight 3,700, dispersity 1.7, calculated glass transition temperature 105°C)

[0132] [Production of acrylic resin (A-1)] In a four-necked round-bottom flask equipped with a reflux condenser, a stirrer, a nitrogen gas inlet, and a thermometer, 1 part of the macromonomer 1 (a1), 90.3 parts of n-butyl acrylate (a2), 8 parts of 2-hydroxyethyl acrylate (a3), 0.7 parts of acrylic acid (a3), 53 parts of ethyl acetate, 42 parts of acetone, and 0.013 parts of azobisisobutyronitrile (AIBN) as a polymerization initiator were charged, and the internal temperature was raised to the boiling point to start the reaction. Next, 30 parts of an ethyl acetate solution containing 0.04% AIBN was added dropwise while reacting at the reflux temperature for 3.25 hours, and then the mixture was diluted with ethyl acetate to obtain an acrylic resin (A-1) solution (solid content 26.2%, viscosity 4,500 mPa·s / 25°C, acrylic resin (A-1): acid value 0.55 mgKOH / g, weight average molecular weight 1.11 million, dispersity 4.0, calculated glass transition temperature -51.6°C).

[0133] [Production of acrylic resin (A-2)] In a four-necked round-bottom flask equipped with a reflux condenser, a stirrer, a nitrogen gas inlet, and a thermometer, 1 part of the macromonomer 2 (a1), 90.3 parts of n-butyl acrylate (a2), 8 parts of 2-hydroxyethyl acrylate (a3), 0.7 parts of acrylic acid (a3), 53 parts of ethyl acetate, 42 parts of acetone, and 0.013 parts of azobisisobutyronitrile (AIBN) as a polymerization initiator were charged, and the internal temperature was raised to the boiling point to start the reaction. Next, 30 parts of an ethyl acetate solution containing 0.04% AIBN was added dropwise while reacting at the reflux temperature for 3.25 hours, and then the mixture was diluted with ethyl acetate to obtain an acrylic resin (A-2) solution (solid content 26.4%, viscosity 9,400 mPa·s / 25°C, acrylic resin (A-2): acid value 0.55 mgKOH / g, weight average molecular weight 1.3 million, dispersity 3.3, calculated glass transition temperature -52.5°C).

[0134] [Production of acrylic resin (A-3)] In a four-necked round-bottom flask equipped with a reflux condenser, a stirrer, a nitrogen gas inlet, and a thermometer, 1 part of the macromonomer 3 (a1), 90.3 parts of n-butyl acrylate (a2), 8 parts of 2-hydroxyethyl acrylate (a3), 0.7 parts of acrylic acid (a3), 53 parts of ethyl acetate, 42 parts of acetone, and 0.013 parts of azobisisobutyronitrile (AIBN) as a polymerization initiator were charged, and the internal temperature was raised to the boiling point to start the reaction. Next, 30 parts of an ethyl acetate solution containing 0.04% AIBN was added dropwise while reacting at the reflux temperature for 3.25 hours, and then the mixture was diluted with ethyl acetate to obtain an acrylic resin (A-3) solution (solid content 26.5%, viscosity 2,385 mPa·s / 25°C, acrylic resin (A-3): acid value 0.55 mgKOH / g, weight average molecular weight 1,030,000, dispersity 3.6, calculated glass transition temperature -51.6°C).

[0135] The monomers used above were from the following manufacturers: n-Butyl acrylate (BA) (Mitsubishi Chemical, glass transition temperature -56°C) 2-Hydroxyethyl acrylate (HEA) (Osaka Organic Chemical Industry Co., Ltd., glass transition temperature -15°C) Acrylic acid (AAc) (Mitsubishi Chemical, glass transition temperature 106°C) The above glass transition temperatures are those of homopolymers of each monomer.

[0136] [Table 1]

[0137] <Ionic Compound (B)> The following was prepared as the ionic compound (B). (B-1): Lithium trifluoromethanesulfonate (Tokyo Chemical Industry Co., Ltd.) (melting point 423°C) (B-2): Lithium N,N-bis(trifluoromethanesulfonyl)imide 56% solution [solvent: tetraethylene glycol dimethyl ether (Sanko Chemical Co., Ltd., Sankonol TGR)] (melting point 235°C) (B'-1): Tributylmethylammonium N,N-bis(trifluoromethanesulfonyl)imide (3M, FC-4400) (melting point 27.5°C)

[0138] <Crosslinking agent (C)> The following was prepared as the crosslinking agent (C). (C-1): Adduct of tolylene diisocyanate and trimethylolpropane (Tosoh Corporation, Coronate L55E)

[0139] <Silane coupling agent (D)> The following silane coupling agent (D) was prepared. The types of reactive functional groups, epoxy equivalent or mercapto equivalent, types of alkoxy groups contained, and alkoxy group content of the silane coupling agent (D) were the values ​​listed in the catalog unless otherwise specified. The weight average molecular weight and dispersity were measured according to the above-mentioned method.

[0140] (D-1): A 1:1 (by weight) mixture of "X-24-9590" and "X-41-1059A" "X-24-9590": Shin-Etsu Chemical Co., Ltd., Reactive functional group: epoxy group, Reactive functional group equivalent: 592 g / mol, Alkoxy group: methoxy group, Alkoxy group content: 9.5%, Weight average molecular weight: 13,700, Dispersity: 3.44 "X-41-1059A": manufactured by Shin-Etsu Chemical Co., Ltd., reactive functional groups: epoxy groups, reactive functional group equivalent: 350 g / mol, alkoxy groups: methoxy and ethoxy groups, alkoxy group content: 42%, weight average molecular weight: 2,270, dispersity: 1.86

[0141] <Examples 1 to 3 and Comparative Examples 1 to 3> The above components were mixed as shown in Table 2 below, and the solid content was adjusted to 15% with ethyl acetate to obtain a pressure-sensitive adhesive composition.

[0142] Using the pressure-sensitive adhesive composition obtained above, evaluation samples were prepared as described below, and the following performances were evaluated. The evaluation results are also shown in Table 2 below.

[0143] [Preparation of polarizing plate with adhesive layer [I]] The obtained adhesive composition was coated onto a 38 μm-thick release sheet (Toray Industries, Therapeel WZ) so that the dried thickness would be 20 μm. After drying at 100° C. for 3 minutes, the adhesive layer surface opposite the release sheet was bonded to one of the triacetyl cellulose (TAC) film surfaces of a polarizing plate having TAC film laminated on both sides, and aged for 7 days in an environment of 23° C. and 50% RH to obtain a polarizing plate with an adhesive layer [I] (layer structure: release sheet / adhesive layer / TAC film 1 / polarizer / TAC film 2). The above TAC films are triacetyl cellulose films, and the thickness of TAC film 1 is 40 μm, and the thickness of TAC film 2 is 40 μm. The pressure-sensitive adhesive layer-attached polarizing plate [I] was subjected to the following evaluations.

[0144] <Durability: Heat resistance test> The obtained polarizing plate with adhesive layer [I] was cut to 165 mm x 95 mm, the release sheet was peeled off, and the adhesive layer surface was pressed against alkali-free glass (Corning Eagle XG, thickness 1.1 mm) and laminated by rolling twice back and forth with a 2 kg roller. After that, the plate was autoclaved (0.5 MPa x 50°C x 20 minutes) to prepare a sample for durability evaluation. The obtained samples were exposed under heat resistance conditions (105° C.×100 hours) and then the polarizing plates were subjected to the following evaluation. (Evaluation Criteria) ◯: No foaming was observed over the entire surface of the polarizing plate or no lifting was observed at the edges, or only very slight lifting was observed at the corners. △: Slight lifting is observed at the edge of the polarizing plate. ×: Bubbles are observed over the entire surface of the polarizing plate or floating of 1 mm or more is observed on the edges.

[0145] <Gel fraction> The release sheet was peeled off from the obtained polarizing plate with an adhesive layer [I], the adhesive was picked from the adhesive layer surface and wrapped in a 200 mesh SUS wire mesh, and then immersed in ethyl acetate adjusted to 23°C for 24 hours. The weight percentage of the insoluble adhesive components remaining in the wire mesh relative to the weight of the adhesive before immersion in ethyl acetate was defined as the gel fraction (%).

[0146] <Antistatic performance: Surface resistivity> The above-mentioned polarizing plate [I] with the adhesive layer was left to stand for 24 hours under an atmosphere of 23°C x 50% RH, after which the release sheet of the adhesive layer was removed and the surface resistivity (Ω / cm 2 ) was measured.

[0147] [Table 2]

[0148] The above results show that in all of Examples 1 to 3, which are pressure-sensitive adhesive compositions containing an acrylic resin (A) containing a structural portion derived from the macromonomer (a1) and an ionic compound (B) having a melting point of 30°C or higher, and which contain a larger amount of the ionic compound (B) relative to the acrylic resin (A), pressure-sensitive adhesives that are capable of achieving both high durability and antistatic performance in high-temperature environments are formed. On the other hand, it is clear that the pressure sensitive adhesives of Comparative Examples 1 to 3, which contained an ionic compound with a low melting point, all had poor durability. Therefore, it is clear that the adhesive obtained by using the adhesive composition of the present invention can achieve both high antistatic performance and high durability even in a high temperature environment.

[0149] Furthermore, since the polarizing plate with an adhesive layer obtained using the adhesive composition of the embodiment of the present invention has both high durability and antistatic performance, it is expected that an image display device obtained by bonding a polarizing plate and an image display member such as a liquid crystal cell via the adhesive layer will be of excellent quality. [Industrial Applicability]

[0150] The adhesive composition of the present invention, when used as an adhesive for bonding a polarizing plate (protective film) to a metal surface of a liquid crystal cell (glass plate) or a conductive layer during the production of a liquid crystal display device, exhibits excellent durability even in a high temperature environment and has excellent antistatic performance, and is therefore useful as an adhesive for optical components for bonding displays and the optical components that constitute them, in particular as an adhesive for polarizing plates for bonding a polarizing plate to a glass substrate of a liquid crystal cell, a substrate equipped with a conductive layer, etc.

Claims

1. A pressure-sensitive adhesive composition comprising an acrylic resin (A) containing a structural portion derived from a macromonomer (a1) and an ionic compound (B), characterized in that the pressure-sensitive adhesive composition contains 3 to 20 parts by weight of the ionic compound (B) per 100 parts by weight of the acrylic resin (A), and the ionic compound (B) has a melting point of 30°C or higher and is an ionic compound whose anion component contains a fluorine atom.

2. 2. The pressure-sensitive adhesive composition according to claim 1, wherein the macromonomer (a1) is an acrylic macromonomer having a structure derived from an alkyl (meth)acrylate and a polar group-containing (meth)acrylate.

3. 3. The pressure-sensitive adhesive composition according to claim 1, wherein the macromonomer (a1) has a number average molecular weight of 1,000 to 50,000.

4. 4. The pressure-sensitive adhesive composition according to claim 1, wherein the content of the macromonomer (a1) is 0.1 to 10% by weight based on the polymerization components constituting the acrylic resin (A).

5. The pressure-sensitive adhesive composition according to any one of claims 1 to 4, characterized in that the acrylic resin (A) is an acrylic resin obtained by polymerizing a polymerization component containing a polar group-containing monomer (a3).

6. 6. The pressure-sensitive adhesive composition according to claim 1, wherein the acrylic resin (A) has an acid value of 30 mgKOH / g or less.

7. 7. The pressure-sensitive adhesive composition according to claim 1, wherein the anion component of the ionic compound (B) is an alkali metal salt of an anion containing a fluorine atom.

8. The pressure-sensitive adhesive composition according to any one of claims 1 to 7, further comprising a crosslinking agent (C).

9. The pressure-sensitive adhesive composition according to any one of claims 1 to 8, further comprising a silane coupling agent (D).

10. A pressure-sensitive adhesive comprising the pressure-sensitive adhesive composition according to any one of claims 1 to 9, which is crosslinked with a crosslinking agent (C).

11. The surface resistivity of the adhesive layer is 1.0×10 10 Ω / cm 2 The adhesive according to claim 10, characterized in that

12. A pressure-sensitive adhesive for polarizing plates, comprising the pressure-sensitive adhesive according to claim 10 or 11.

13. 12. An image display device comprising a polarizing plate and an image display member bonded together with the pressure-sensitive adhesive according to claim 10 or 11.

Citation Information

Patent Citations

  • Manufacture of laminated board

    JP1985042036A

  • Acrylic adhesive composition

    JP1996143847A

  • Pressure-sensitive adhesive for liquid crystal element and liquid crystal element

    JP1996209095A

  • Resin film with self-adhesive and optical laminate using the same

    JP2009079205A

  • Pressure sensitive adhesive composition, pressure sensitive adhesive and optical film

    JP2011105830A